Stress in Parents of Children With Genetically Determined Leukoencephalopathies: A Pilot Study. (November 2020) - Dermer, E.; Spahr, A.; Tran, L. T.; Mirchi, A.; Pelletier, F.; Guerrero, K.; Ahmed, S.; Brais, B.; Braverman, N.; Buhas, D.; Chandratre, S.; Chenier, S.; et al.
Genetically determined leukoencephalopathies comprise a group of rare inherited white matter disorders. The majority are progressive diseases resulting in early death. We performed a cross-sectional pilot study including 55 parents from 36 families to assess the level of stress experienced by parents of patients with genetically determined leukoencephalopathies, aged 1 month to 12 years. Thirty-four mothers and 21 fathers completed the Parenting Stress Index–4th Edition. One demographic questionnaire was completed per family. Detailed clinical data was gathered on all patients. Statistical analysis was performed with total stress percentile score as the primary outcome. Mothers and fathers had significantly higher stress levels compared with the normative sample; 20% of parents had high levels of stress whereas 11% had clinically significant levels of stress. Mothers and fathers had comparable total stress percentile scores. We identified pediatric behavioral difficulties and gross motor function to be factors influencing stress in mothers. Our study is the first to examine parental stress in this population and highlights the need for parental support early in the disease course. In this pilot study, we demonstrated that using the Parenting Stress Index–4th Edition to assess stress levels in parents of patients with genetically determined leukoencephalopathies is feasible, leads to valuable and actionable results, and should be used in larger, prospective studies.